ANALISIS SEBARAN OMZET USAHA DI SEKITAR KAWASAN UNIVERSITAS SAMUDRA - Hafizh, Yadi; Urfan, Faiz (Jurnal Samudra Geografi, 2024)
This research aims to analyze the distribution of businesses and business turnover around the Samudra University campus area. This research uses a quantitative approach with spatial analysis techniques. The data collected in this research is the type of business and business turnover according to day and time. The data analysis technique used is Inverse Distance Weighting (IDW). This analysis is used to map the distribution of business turnover using the Quantum GIS (QGIS) application version 3.34. The results of this research are in the form of geospatial information about the distribution of business turnover. There are differences in turnover between one business and another. Businesses with the highest turnover are in areas far from campus. Meanwhile, businesses located near campus have lower turnover. This is caused by the activities of students who move to campus to eat breakfast or lunch. Therefore, researchers recommend building good roads around the UNSAM campus area for more equitable economic development.